Enhancing Early Childhood Islamic Values Through Interactive Learning at RA Baabussalam Tapos Depok - Heni Hartati; Roliani (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This Classroom Action Research (CAR) aims to enhance the understanding of Islamic values among young children in RA Baabussalam Tapos Depok through interactive learning methods. Early childhood education plays a significant role in shaping the character and religious values of children, and it is essential to introduce Islamic teachings effectively at this stage. The research focuses on the application of interactive learning techniques that engage students actively in acquiring Islamic knowledge. Methods such as storytelling, role-playing, and games are incorporated to make the learning process more enjoyable and meaningful. These methods are expected to foster a deeper understanding of Islamic values, such as honesty, kindness, and respect, which are crucial for the moral development of children. The research was conducted in two cycles, each consisting of planning, action, observation, and reflection stages. Data was collected through observations, interviews with teachers, and feedback from the students. The results indicate that interactive learning methods significantly improved the students’ participation and understanding of Islamic teachings. Children became more engaged during lessons, and there was a noticeable improvement in their ability to express and apply Islamic values in their daily lives. Teachers also reported a positive change in their teaching approach, which led to a more effective classroom environment. This study suggests that incorporating interactive learning methods in early childhood education can be a powerful tool to instill Islamic values in young children. It also highlights the importance of adapting teaching strategies to the developmental needs of children to ensure that Islamic education is not only informative but also enjoyable and relatable.